First-principles study on the interfacial bonding strength and segregation at Mg/MgZn2 matrix interface - Longke Bao; Peng Du; Shengkun Xi; Cuiping Wang; Kaihong Zheng; Rongpei Shi; Guoqiang Xie; Xingjun Liu (Journal of Magnesium and Alloys)
To understand the interface characteristics between the precipitate β2′ and the Mg matrix, and thus guide the development of new Mg-Zn alloys, we investigated the atomic interface structure, work of adhesion (Wad), and interfacial energy (γ) of Mg(0001)/β2'(MgZn2)(0001) interface, as well as the effect of segregation behavior of the introduced transition metal atoms (3d, 4d and 5d) on interfacial bonding strength. The calculated works of adhesion and interfacial energies dementated that the Zn2-terminated MT+HCP configuration is the most stable structure for all considered models. Take the Zn2- MT+HCP interface as the research object, estimated segregated energies (Eseg) reveal that added transition metal atoms prefer to segregate at Mg-I and Mg-II sites. The predicted Wad and charge density difference results reveal that the segregation of alloying additives employed may all strengthen Mg(0001)/MgZn2(0001) interface, with the enhancement effect of Os, Re, Tc, W, and Ru at the Mg-II site being the most pronounced.